2021
DOI: 10.1002/ehf2.13320
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed measurement of candidate blood protein biomarkers of heart failure

Abstract: Aims There is a critical need for better biomarkers so that heart failure can be diagnosed at an earlier stage and with greater accuracy. The purpose of this study was to design a robust mass spectrometry (MS)-based assay for the simultaneous measurement of a panel of 35 candidate protein biomarkers of heart failure, in blood. The overall aim was to evaluate the potential clinical utility of this biomarker panel for prediction of heart failure in a cohort of 500 patients. Methods and results Multiple reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The up-regulated genes include Apolipoprotein A1 (APOA1), a main protein in high-density lipoprotein (HDL) (20), but many of the other genes related to lipid metabolism have rarely been reported. Another study also found that APOA1 was significantly differentially expressed between non-heart failure and heart failure patients, and could be a candidate blood protein biomarker of heart failure (21). The present study identified numerous DELs associated with DCM, which could be potential targets for subsequent research.…”
Section: Discussionsupporting
confidence: 55%
“…The up-regulated genes include Apolipoprotein A1 (APOA1), a main protein in high-density lipoprotein (HDL) (20), but many of the other genes related to lipid metabolism have rarely been reported. Another study also found that APOA1 was significantly differentially expressed between non-heart failure and heart failure patients, and could be a candidate blood protein biomarker of heart failure (21). The present study identified numerous DELs associated with DCM, which could be potential targets for subsequent research.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, female study participants showed higher LRG1 levels than males [ 113 , 114 ] which supports other findings suggesting there are sex differences in the biology of LRG1. Other studies reported a positive correlation between circulating or coronary sinus LRG1 levels and the incidence of heart failure [ 115 118 ] and idiopathic pulmonary arterial hypertension [ 119 ]. In contrast, in patients with statin-treated familial hypercholesteremia, detectable serum levels of LRG1 were observed only in the absence of coronary artery disease [ 120 ].…”
Section: Reviewmentioning
confidence: 99%
“…LRG1 might be a potential serum biomarker for early onset myocardial infarction, while a combined biomarker signature that included BNP (plasma brain natriuretic peptide) would be a more accurate predictor of heart failure than BNP alone (Xuan et al, 2019). TLRG1 was the most prominent biomarker, among others, to predict the pathological progress of heart failure (Tonry et al, 2021). LRG1 was selected to distinguish persistent atrial fibrillation patients and control subjects (Cao et al, 2020).…”
Section: Part Seven: Lrg1 Involved In Cardiovascular Diseasesmentioning
confidence: 99%
“…Due to their great potential in the prediction of cardiovascular diseases, particular methods and mechanisms had yet to be investigated. Uncovering potential lncRNAs and mRNAs, including LRG1 was essential biomarkers from acute myocardial infarction aggravated to heart failure (Tonry et al, 2021;Wang et al, 2021). In terms of mechanism research, overexpressed miR-494 bound with LRG1 inactivated Wnt signaling pathway might promote fibroblasts and vascular endothelial cells proliferation in myocardial infarction (Su et al, 2019).…”
Section: Part Seven: Lrg1 Involved In Cardiovascular Diseasesmentioning
confidence: 99%